2019
DOI: 10.5465/amle.2017.0351
|View full text |Cite
|
Sign up to set email alerts
|

Who Built Maslow’s Pyramid? A History of the Creation of Management Studies’ Most Famous Symbol and Its Implications for Management Education

Abstract: Abraham Maslow's theory of motivation, the idea that human needs exist in a hierarchy that people strive to satisfy progressively, is regarded as a fundamental approach to understanding and motivating people at work. It is one of the first and most remembered models encountered by students of management. Despite gaining little support in empirical studies and being criticized for promoting an elitist, individualistic view of management, Maslow's theory remains popular, underpinned by its widely recognized pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 61 publications
1
45
0
17
Order By: Relevance
“…Even though the popularity of Maslow's theory is partly attributed to the iconic appeal of the pyramid (or, more accurately, the triangle), Maslow himself never used the triangle image. In a recent paper, Bridgman, Cummings, and Ballard [34] traced the origins of the triangle visualisation to a manuscript of the consulting psychologist Charles McDermid [35]. After that, the image was popularized by management textbooks.…”
Section: )mentioning
confidence: 99%
“…Even though the popularity of Maslow's theory is partly attributed to the iconic appeal of the pyramid (or, more accurately, the triangle), Maslow himself never used the triangle image. In a recent paper, Bridgman, Cummings, and Ballard [34] traced the origins of the triangle visualisation to a manuscript of the consulting psychologist Charles McDermid [35]. After that, the image was popularized by management textbooks.…”
Section: )mentioning
confidence: 99%
“…Two recent examples strike me as interesting for being consensus-breaking and conversation-starting: Cummings et al (2016), for instance, analyzed historical records to find that Kurt Lewin never did create the popular model of change managementof unfreezing, change and refreezingeven if many have acknowledged him as the creator of such a model; in a similar vein, Bridgman et al (2019) found that Abraham Maslow never did draw the ubiquitous pyramid of needs that has so captured the imagination of theoreticians and practitioners alike. The point is that these studies encourage readers to question conventional wisdom and assumptions, and open up new ways of thinking.…”
Section: Contributionmentioning
confidence: 99%
“…This framework is perhaps best recognised through what has been called Maslow's model of a hierarchy of needs, and this is often the form in which the theoretical framework is used in research studies. The creation and use of this model for underpinning research has been strongly questioned (Bridgman, Cummings, & Ballard, 2019); again, the background theories that led to this framework contextualise it in important ways.…”
Section: Description Examplesmentioning
confidence: 99%